PENGARUH PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI PERIODE 2019-2022 - Qumariah, Nurul; Arief, Mohammad Yahya; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2024)
Food and beverage subsector companies are pillars of a country’s economy, therefore the food and beverage subsector plays an important role in driving the wheels of the Indonesian economy, to boosr productivity and the abilitu og the sector to compete globally, the government is still working hard to ensure the stability and availability of raw materials needed by the food and beverage subsector. The purpose of this study was to examine the effect of profitability, and company growth in influencing the company’s value moderated by capital structure. This research is explanatory research. The population in this study were food and beverage subsector companies listed on the Indonesia Stock Exchange 2019-2022. The sampling technique is purposive sampling. Data analysis and hypothesis testing using the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Snart PLS 3.0 application show that profitability has a significant positive effect on firm value, campany growth has a insignificant positive effect on firm value, capital structure is able to moderate the effect of profitability on firm value, capital structure is not able to moderate the effect of company growth ob firm value.